P647 Idiopathic Thrombocytopenic Purpura associated with Inflammatory Bowel Disease: a multi-centre ECCO CONFER case series. (21st January 2022) - Mahajna, H; Verstockt, B; Bergemalm, D; Castiglione, F; Rodríguez-Moranta, F; Vincenzo Savarino, E; Hoentjen, F; Bessissow, T; Pokryszka, J; Cremer, A; Eder, P; Truyens, M; et al.
Abstract: Background: Idiopathic Thrombocytopenic Purpura (ITP) is an acquired haematological disorder with an incidence of 1 to 6 per 100.000, with reported comorbidity in patients with Inflammatory Bowel Disease (IBD). The current study aimed to evaluate the clinical presentation and outcome of ITP in IBD patients. Methods: This multicenter retrospective case series was performed as part of the ECCO Collaborative Network of Exceptionally Rare case reports (CONFER) project. Cases of patients with ITP and IBD were collected by participating investigators. Clinical data were recorded in a standardised collection form. Results: This report includes 20 patients with concurrent ITP and IBD: 15 were males, median age was 34 [Interquartile range (IQR) 25–56]. 12 subjects had a diagnosis of ulcerative colitis and 8 of Crohn's disease. The diagnosis of IBD preceded the ITP diagnosis in 17 patients (median time between diagnosis was 7 years [IQR 1–14 years]). Among those, 10 patients were in IBD clinical remission at ITP diagnosis. Nine were treated with mesalamine, one with thiopurine, 4 with tumor necrosis factor-alpha (TNF) blockers, and 3 with no treatment. The mean platelet count at the presentation of ITP was 41.7±38.6 ×10 9 /L. 6 patients had rectal bleeding, 8 had purpura, 6 had mucosal petechia, 2 had epistaxis, and 6 patients were asymptomatic. Regarding ITP treatment, 11 were treated with corticosteroids, 1 with Anti-RhD immunoglobulin, 7 with intravenous immunoglobulins (IVIG), 2 with rituximab and 2 patients eventually required splenectomy. All patients whose first presentation of ITP was rectal bleeding were treated medically with successful control of the ITP and IBD, None of them required splenectomy. 3 patients required colectomy with long-term follow-up, indicated by the IBD and not due to massive bleeding as a complication of ITP. With long-term follow-up, all patients had thrombocytes count above 50 ×10 9 /L, and 18 were in IBD clinical remission. Conclusion: Most ITP cases in this case series occurred after the IBD diagnosis and responded well to regular ITP treatment. The course of the ITP in the IBD patients follows a regular course, including response to medical therapy and low rates of splenectomy.